Officina Asia ReteEmiliaRomagna - Barilli, Renato; Galleria d'Arte Moderna, Bologna; Galleria Comunale d'Arte - Palazzo del Ridotto e Galleria d'Arte Ex-Pescheria, Cesena; Palazzo dell' Arengo, Rimini (Bologna Milano : Edizioni Gabriele Mazzotta Milano Galleria d'Arte Moderna Bologna, 2004)
Aida Makoto ; Akira Yamaguchi ; Aoyama, Satori ; Bai Yiluo ; Boomoon ; Cheong Kwang-Ho ; Choe U-Ram ; Gwon Osang ; He Yunchang ; Higashionna, Yuichi ; Hirose, Satoshi ; Hong Seung-Hye ; Huang Yan ; Hwang Insook ; Karasumaru, Yumi ; Kim Hong-Joo ; Kim Jongku ; Konoike, Tomoko ; Lin Tianmiao ; Liu Jin ; Li Yongbin ; Li Wei ; Ma Han ; Ma Yunfei ; Matsue, Taiji ; Matsukage, Hiroyuki ; Mika Kato ; Miyake, Shintaro ; Motomiya, Kaori ; Muneteru Ujino ; Murayama, Ruriko ; Nam Zie ; Nishiyama, Minako ; Nobuya Hoki ; Ogai & Ogawa ; Sato, Shinako ; Shibuya, Kiyomichi ; Song Dong ; Seungho, Yoo ; Suda, Yoshihiro ; Tanaka, Koki ; Wang Gong Xin ; Wang Mai ; Wang Qingsong ; Wang Shugang ; Watanabe, Hidehiro ; Whang Inkie ; Yamaguchi, Ai ; Yihui, Xu ; Yim Ja-Hyuk ; Yin Xiuzhen ; Zhang Xiaotao ; Zhao Liang ; Zhou Jirong
Biog., ind. tent., gr. tent. p. 185-201
Works in the exhibition p. 202-207
Published on the occasion of the exhibition "Officina Asia" at the Galleria d'Arte Moderna in Bologna, 06.06.2004 - 05.09.2004 and at the Galleria Comunale d'Arte - Palazzo del Ridotto e Galleria d'Arte Ex-Pescheria in Cesena, 06.06.2004 - 05.09.2004 and at the Palazzo dell' Arengo in Rimini, 06.06.2004 - 29.08.2004
boek